The use of personal protective equipment by the employees in COVID-19 Departments of the University Clinical Center of Republic of Srpska and the risk assessment of the new coronavirus - Janja Bojanić; Silvana Trifunović; Antonija Verhaz; Darija Knežević; Mirjana Djermanović; Nataša Knežević; Mladena Malinović (Биомедицинска истраживања, 2022)
Introduction: Assessment of the occupational risk of exposure to the new coronavirus of workers engaged in the COVID-19 Departments of the University Clinical Center of Republic of Srpska and the use of personal protective equipment was the aim of this research. Method: In the University Clinical Center of Republic of Srpska (UKC RS), in the COVID-19 Departments, a KAP study (Knowledge Attitudes Practice Study) was conducted among 102 employees of all educational profiles, using the questionnaire of the World Health Organization (WHO), which was adapted for this research. The survey was voluntary and anonymous with the informed approval consent of the respondent. Results: Out of 102 surveyed, 13 of them tested positive for SARSCoV-2. On average, 95.0% of respondents always wear PPE in the COVID-19 Departments of the UKC RS. Putting on/removing PPE and decontamination of contact surfaces have been always carried out by 88.2% of respondents. Out of 64 respondents who used PPE for aerosol generating procedures, 10 of them (15.6%) were positive for SARSCoV-2 and of the other 38 respondents who did not participate in such procedures, three of them (7.9%) were positive for SARS-CoV-2. Statistical data processing was done in the SPSS program package, version 20.0, with a significance level of difference of 5% (p=0.412). Conclusion: There was no significant difference between SARSCoV-2 positive and negative personnel regarding the use and change of PPE, hand hygiene and surface decontamination. The assessment of the occupational risk of exposure to SARS-CoV-2, in addition to the proper use of PPE, takes into account the local epidemiological situation, specific characteristics of the work environment and tasks, the hierarchy of controls and the level of adherence to preventive measures and infection control.
Keywords: pandemic; new coronavirus; personal protective equipment